Targeting endothelial cells: the pathological mechanisms and therapeutic innovations in pulmonary arterial hypertension - Fan, Tianfei; Li, Longji; Wang, Yao; Lin, Meng; Wu, Fengbo (Frontiers in Cell and Developmental Biology, 2025)
Pulmonary arterial hypertension (PAH) is a fatal disease with high mortality, which is characterized by pulmonary vascular remodeling. Current clinical treatments mainly focus on dilating vascular and relieving pulmonary artery pressure. However, there is still no effective treatment available to reverse vascular remodeling. Endothelial cells (ECs) play an important role in vascular function and repair. Endothelial dysfunction is a key factor inducing vascular remodeling and PAH. The endothelial - mesenchymal transition (EndMT), along with the abnormal apoptosis and proliferation of endothelial cells (ECs) disrupt vascular homeostasis and drive pulmonary artery remodeling. These regulated by the TGF - β/BMP, PI3K/Akt, and JAK - STAT pathways. Moreover, the secretion of active factors by ECs and the crosstalk between ECs and smooth muscle cells (SMCs) also influence vascular remodeling. Targeting ECs shows certain application prospects in the treatment and diagnosis of PAH. This article elaborates on the role and mechanisms of ECs in PAH, and reviews their diagnostic markers and therapeutic targets for the early intervention and effective management of PAH.